Cognitive Development in Bottle Versus Breastfed Children up to Two Years: A Comparative Study from Islamabad - Bilal, Arshia; Afzal, Asifa; Malik, Iqra Zaheer; Ishtiaq, Faryal; Ahmad, Ayesha; Rashid, Ayesha; Fatima, Insha; Waheed, Anaam (Pakistan Armed Forces Medical Journal, 2023)
Objectives: To evaluate the proportion of exclusively breastfeeding and to determine the association of various types of feeding with cognitive development in children up to two years of age.Study Design: Cross-sectional analytical study.Place and Duration of Study: Outpatient Department of Pediatrics, Pakistan Air Force Hospital, Islamabad Pakistan, from Jan to Aug 2019.Methodology: Mothers of children under two years of age visiting the hospital were recruited by systematic sampling. The data was collected through interviews using a semi-structured questionnaire. A score of each child has dichotomized into satisfactory and unsatisfactory cognitive development overall and separately for each domain viz communication, fine motor, gross motor, problem-solving and personal social skills.Results: Out of 192 children, less than half, 77(40.1), were exclusively breastfed. Feeding practices had a statistically significant effect on overall cognitive development (p